THE DEVELOPMENT OF ORGANIZATION CULTURE : A CASE STUDY OF FACULTY OF LIBERAL ARTS, RAJAMANGALA UNIVERSITY OF TECHNOLOGY SUVARNABHUMI - Thodthankhun, Thanu (Journal of MCU Social Science Review, 2017)
This research has purposes to 1) study the history of organization culture of the Faculty of Liberal Arts, Rajamangala University of Technology Suvarnabhumi (RUS) culture of Faculty of Liberal Arts, RUS. The research used qualitative research methodology by collecting data from documents and field data. The research areas were selected by purposive sampling method comprised of the departments within the Faculty of Arts, RUS whereas populations and samples of the study included government officials, administrators, academic and support staffs, government employees, employees of the Faculty of Liberal Arts, RUS which were 40 people in total. Research instruments included observation, interview, group discussion and workshop. The obtained data was validated by using triangular validation techniques, analyzed the qualitative data for the purpose of research and present the results by descriptive method. The research found that the history and past culture of the Faculty of Liberal Arts Suvarnabhumi contains organizational culture in 6 areas: 1) Communication; 2) Discipline; 3) Public Mind; 4) Participation; 5) Democracy in organization and 6) Harmony. In the past, they treated each other as a tangible network that there were regular inter-agency activities within the center. Members of the organization must be subject to official regulations. They supported each others at all time, had a brotherhood-liked relationship and respected the seniors in the organization as their elder relative. Considering the current situation, problems, and guidelines for the development of organization culture of Faculty of Liberal Arts, RUS, The researcher separately presented the results of the study in two issues as : the current organizational culture of the organization, current organization culture issues and the development of organization culture of the Faculty of Arts, RUS as an overview of organization culture in 6 areas. It found that the forms of communication, both formal and informal, are channels for multi-channel communication such as telephones, faxes and government documents with a modern information technology with explicitly defined rules of both personnel and students. All members of the organization are subject to government regulations and must comply with the rules determined. There is a providing of personnel development projects in the field of morality and ethics with purposes to ;) increase the knowledge of the work and to adjust the attitude of the personnel within the faculty to aware of the service mind on a continuous basis continually ;) to encourage the collaboration in evaluating the effectiveness of the organization to make the organization more efficient by engaging personnel in internal and external environmental analysis to identify strengths, weakness, opportunities, and obstacles to determine visions for joint development and) to uphold democratic principles in administration by encouraging personnel to work more as a team. All of the mention above leads to the development of organizational culture of the Faculty of Arts, RUS as an overview of organization cultures in 6 areas as follows: 1) to raise awareness and promote morality and ethics in receiving and transmitting information between each other accurately, completely and creatively;2) provide organizational learning and understand rules better and 3) organize training sessions for new government regulations and campaign to follow the rules including to cultivate the personnel to understand and realize that they are a part and a vital part of organizational development. The activities / projects should be organized to learn the differences in the thinking of each age group as well as organizing activities to strengthen relations between personnel.